Tethering of CHROMATOR and dCTCF proteins results in decompaction of condensed bands in the Drosophila melanogaster polytene chromosomes but does not affect their transcription and replication timing. - Pokholkova, G.V.; Demakov, S.A.; Andreenkov, O.V.; Andreenkova, N.G.; Volkova, E.I.; Belyaeva, E.S.; Zhimulev, I.F. (PLoS ONE, 2018)
Instulator proteins are central to domain organization and gene regulation in the genome. We used ectopic tethering of CHROMATOR (CHRIZ/CHRO) and dCTCF to pre-defined regions of the genome to dissect the influence of these proteins on local chromatin organization, to analyze their interaction with other key chromatin proteins and to evaluate the effects on transcription and replication. Specifically, using UAS-GAL4DBD system, CHRO and dCTCF were artificially recruited into highly compacted polytene chromosome bands that share the features of silent chromatin type known as intercalary heterochromatin (IH). This led to local chromatin decondensation, formation of novel DHSes and recruitment of several "open chromatin" proteins. CHRO tethering resulted in the recruitment of CP190 and Z4 (PZG), whereas dCTCF tethering attracted CHRO, CP190, and Z4. Importantly, formation of a local stretch of open chromatin did not result in the reactivation of silent marker genes yellow and mini-white immediately adjacent to the targeting region (UAS), nor did RNA polII become recruited into this chromatin. The decompacted region retained late replicated, similarly to the wild-type untargeted region.